2016
DOI: 10.1080/10962247.2016.1141808
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds at two oil and natural gas production well pads in Colorado and Texas using passive samplers

Abstract: A pilot study was conducted in application of the U.S. Environmental Protection Agency (EPA) Methods 325A/B variant for monitoring volatile organic compounds (VOCs) near two oil and natural gas (ONG) production well pads in the Texas Barnett Shale formation and Colorado Denver-Julesburg Basin (DJB), along with a traffic-dominated site in downtown Denver, CO. As indicated in the EPA method, VOC concentrations were measured for 14-day sampling periods using passive-diffusive tube samplers with Carbopack X sorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 21 publications
(27 reference statements)
2
20
0
Order By: Relevance
“…et al, 2014 [ 71 ] Mobile measurement of methane and hydrogen sulfide at natural gas production site fence lines in the Texas Barnett Shale Barnett Eisele, AP. et al, 2016 [ 72 ] Volatile organic compounds at two oil and natural gas production well pads in Colorado and Texas using passive samplers Barnett; Denver-Julesburg Esswein, EJ. et al, 2014 [ 73 ] Evaluation of some potential chemical exposure risks during flowback operations in unconventional oil and gas extraction: Preliminary results Denver-Julesburg; Green River; Piceance Field, RA.…”
Section: Resultsmentioning
confidence: 99%
“…et al, 2014 [ 71 ] Mobile measurement of methane and hydrogen sulfide at natural gas production site fence lines in the Texas Barnett Shale Barnett Eisele, AP. et al, 2016 [ 72 ] Volatile organic compounds at two oil and natural gas production well pads in Colorado and Texas using passive samplers Barnett; Denver-Julesburg Esswein, EJ. et al, 2014 [ 73 ] Evaluation of some potential chemical exposure risks during flowback operations in unconventional oil and gas extraction: Preliminary results Denver-Julesburg; Green River; Piceance Field, RA.…”
Section: Resultsmentioning
confidence: 99%
“…General information on EPA's use of passive samplers, including deployment methods, validation comparisons, and laboratory analysis and analytical components, is described elsewhere (Eisele et al, 2016;McClenny et al, 2005McClenny et al, , 2006Mukerjee et al, 2009;Thoma et al, 2011Thoma et al, , 2015, with specific details of the Philadelphia passive sampler and sensor study in Thoma et al (2015). With the exception of deployment locations, sampling methods applied were similar to EPA Methods 325A and 325B (EPA, 2015a;2015b).…”
Section: Methodsmentioning
confidence: 99%
“…Continuing these near-source monitoring efforts, the EPA recently conducted VOC monitoring studies using Carbopack X passive sampling tubes at sites near and away from fenceline locations at a petroleum refinery and other operations in South Philadelphia (Thoma et al, 2015) and at oil and natural gas operations (Eisele et al, 2016). This paper details the results of the South Philadelphia study in terms of spatial gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Of the chemical hazards, the process of OG extraction releases volatile organic compounds (VOCs) directly into the air. Multiple studies have identified several VOCs in the air near OG operations in Colorado [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Some of these VOCs are categorized as hazardous air pollutants by the U.S. EPA and Colorado Regulation 3 (5 CCR 1001-5) due to their potential to cause adverse health effects, such as cancer, neurological, developmental and reproductive effects and some have the capacity to alter endocrine activity at some exposure level [ 24 ].…”
Section: Introductionmentioning
confidence: 99%